Vaginal balls: Therapeutic function - Miriam Abdel Karim Ruiz (Universidad de Alicante, 2015)
Introduction: Vaginal spheres are also known as Chinese balls, vaginal balls, love balls, geisha balls, Rin no tama, Ben Wa balls. Help strengthen the pelvic floor. These produce a microvibration to move the ball inside, favoring the pelvic floor muscles and increasing blood flow to the pelvic region. There are different areas of weight, torque indications pelvic floor should be tonic. Objective: To review the literature on the effectiveness of vaginal balls and increase knowledge of the professionals on this kind of proprioceptive therapy, which is effective for many women for its easy use. Methods: Literature search in databases: Cochrane, Medline, Gerion, SciELO, Take care, Reproductive Health Library WHO and Academic Google. Results: The vaginal balls are effective in the treatment of urinary and fecal incontinence and pelvic floor training. Urinary incontinence is a common and distressing problem, which may interfere in the work, social and sexual life. There is need for further trials to evaluate the methods and protocols of adequate training for the prevention of incontinence, prolapse and sexual dysfunction. Conclusion: It has been shown that vaginal are better than no active treatment in women with stress urinary incontinence and can be equally effective than pelvic floor muscle training and electrical stimulation.